Trayectorias migrantes: la juventud venezolana en el Perú. Resumen ejecutivo - Salmón, Elizabeth (2022)
Investigadores: Cécile Blouin, Stéphanie Borios, Robin Cavagnoud, Gonzalo Gamio Gheri, Marcela Huaita Alegre, Elizabeth Salmón, Pablo Vega Romá, Crisbeth Vigo